De Alemania a México: Samuel Chávez y la gimnasia rítmica del Instituto Dalcroze, 1912-1922 - Sifuentes Solís, Marco Alejandro; García Díaz, Jorge Refugio; Acosta Collazo, Alejandro (Anuario de Historia de América Latina, 2021)
The main objective of this article is to make known to the community of historians, especially architecture historians, a little explored facet of the architect Samuel Chávez (a native of the city of Aguascalientes but whose professional development was centered in Mexico City), consisting of the interest he maintained in the relationship between architecture, dance and music. To this end, the text offers historical evidence and arguments based both on the interpretation of a corpus of documents from his personal archive (which as far as is known has not been worked on by the specialized historiography), as on the hemerography of the time and the current bibliography. Beyond what Raquel Tibol (1984) affirmed, in the sense of considering Samuel Chávez as one of the forerunners of modern dance in Mexico, our contribution consists of documenting, in a contextualized way, the meeting point of the architect with the key pedagogical center of the movements for the reform of life: the Jaques Dalcroze Institute of Rhythmics, located in the German garden city of Hellerau, which was a turning point in the professional career of Chávez as he freed himself from the bonds of his former Beaux-arts training, and thus linked him to the European avant-garde of the moment. Our article only focuses on the period 1912-1922.